Faster than Books and More Involved than Movies: Understanding the Contemporary Reading Experience of Young Adult Readers of Graphic Novels and Comic Books - Cedeira Serantes, Lucia (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This project looks at the reading experience of young adult readers of comic books and graphic novels. A phenomelogical standpoint implemented through semi-structured interviews allows for the exploration of the readers’ perception of the comics medium, their understanding of the reading experience, and the role of bookstores and libraries in their reading practices. Ce projet explore l’expérience de lecture de comic books et de romans graphiques des jeunes adultes. Une approche phénoménologique a été mise en œuvre au moyen d’entrevues semi-structurées pour découvrir les perceptions qu’ont les lecteurs des comic books, leur compréhension de l’expérience de lecture et le rôle des librairies et des bibliothèques sur leur pratique de lecture.